If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -6 = 2n + 20 Reorder the terms: -6 + 6n = 2n + 20 Reorder the terms: -6 + 6n = 20 + 2n Solving -6 + 6n = 20 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -6 + 6n + -2n = 20 + 2n + -2n Combine like terms: 6n + -2n = 4n -6 + 4n = 20 + 2n + -2n Combine like terms: 2n + -2n = 0 -6 + 4n = 20 + 0 -6 + 4n = 20 Add '6' to each side of the equation. -6 + 6 + 4n = 20 + 6 Combine like terms: -6 + 6 = 0 0 + 4n = 20 + 6 4n = 20 + 6 Combine like terms: 20 + 6 = 26 4n = 26 Divide each side by '4'. n = 6.5 Simplifying n = 6.5
| 4-3x=9+x-5x | | .75=0.4p+100 | | 0.25+y=225 | | 1.66x-9=61x-201 | | 3m=2(4+x)salveforx | | 5x-3*5=15 | | 9x-40=7x-37 | | (x+14)+3x=180 | | 19-3n=13 | | -37+6x=19+2x | | 3p+5q=7 | | 6+5g=3g+20 | | 4x-10=7x-9 | | 10=0.83(n+6) | | 2-(-2)s=6 | | -x-18=36 | | 0.5x+.01x+12+1x-5=9.96 | | 3d+4(-3)=11 | | 2661=63+63(n-1) | | x^2-kx+9=y | | 4x+3a=bx+2.5a-5 | | 5(x+3)-2=2x+9 | | 6x+8x-42=84-7x | | v-7.5=3.4 | | x^2+9x=15 | | 3r+1=r+8 | | 5r+7=-13+7r | | 9d+4(-7)=15 | | -7+4(1-5x)=x+39 | | y+6.4=9.66 | | X+50=76 | | 63=9(z-92) |